Patient journey to a specialist amyotrophic lateral sclerosis multidisciplinary clinic: an exploratory study. - Hardiman, Orla; Galvin, Miriam (My University, 2015)
BACKGROUND: The multidisciplinary approach in the management of Amyotrophic Lateral Sclerosis (ALS) has been shown to provide superior care to devolved care, with better survival, improved quality of care, and quality of life. Access to expert multidisciplinary management should be a standard for patients with ALS. This analysis explores the patient journey from symptom onset and first engagement with health services, to the initial visit to a specialist ALS Multidisciplinary Clinic (MDC) in Dublin, Ireland. METHODS: A retrospective exploratory multi-method study details the patient journey to the MDC. Data from medical interviews and systematic chart review identifies interactions with the health services and key timelines for thirty five new patients presenting with a diagnosis of ALS during a 6 month period in 2013. RESULTS: The time from first symptom to diagnosis was a mean of 16 months (median 13 months), with a mean interval of 19 months (median 14.6) from first symptoms to arrival at the MDC. The majority of patients were seen by a general practitioner, and subsequently by neurology services. There was an average of four contacts with health services and 4.8 investigations/tests, prior to their first Clinic visit. On the first visit to the MDC patients are linked into an integrated 'system' that can provide specialist care and link with voluntary, palliative and community services as required. CONCLUSIONS: Engagement with a multidisciplinary team has implications for service utilization and quality of life of patients and their families. We have demonstrated that barriers exist that delay referral to specialist services. Comprehensive data recording and collection, using multiple data sources can reconstruct the timelines of the patient journey, which can in turn be used to identify pathways that can expedite early referral to specialist services.
PUBLISHED
Keywords: Amyotrophic Lateral Sclerosis (ALS)